Teacher Autonomy Support Influence on Online Learning Engagement: The Mediating Roles of Self-Efficacy and Self-Regulated Learning - Jia Miao; Li Ma (SAGE Open, 2023)
Higher education faculty’s autonomous support of online teaching can promote students engagement in online context. This study collected 492 Chinese university students’ survey questionnaires and applied structural equation model to measure their teacher autonomy support, self-efficacy, self-regulated learning (SRL), and online learning engagement. This study adopted self-determination theory (SDT), systematically explored the relationship between teachers’ autonomy support and student learning engagement from the perspective of online contexts, and examined the mediating effects of students’ self-efficacy and self-regulated learning (SRL) in online contexts. This study found that teacher autonomy support had a significant effect on student engagement in online learning, and was mediated by self-efficacy. Teacher-directed support had a significant effect on student engagement in online learning mediated by SRL. Teacher-directed support had a significant impact on online learning with self-efficacy and SRL as the main mediating variables. Therefore, this study gave a fresh perspective to improve students’ online learning engagement, that is to say, teachers were encourage to improve students’ autonomy in practical teaching on the basis of giving students autonomy support. Students can promote online learning engagement by strengthening self-efficacy and self-regulation through organizational exchanges and mutual assistance and cooperation of students.